SMART BIOMATERIALS - A REVIEW - Bhullar, Sukhwinder Kaur; Lala, Neeta L.; Ramkrishna, Seeram (Sciendo, 2015)
Smart biomaterials are designed to act as an 'on-off' switch for various applications from macro- to nanometer scale which self-heals or responds to the changes in the environment when one of its property changes by the external conditions like temperature, light, pressure or electricity. This change is reversible and can be repeated for several times. When used for healthcare, it improves its performances in medical devices thus promoting desired biological responses like healing, tissue growth etc. Smart materials can deliver therapeutics to the designated site of the body. It is a challenging task to sketch out the classification of smart materials due to its different approaches and quantity of publications related to this topic, is almost impossible to provide a comprehensive review. There are various types of smart materials namely piezoelectric materials, shape memory polymers or alloys, temperature responsive polymers, photomechanical materials, self-healing materials, thermoelectric materials etc. The current review has been focused on smart biomaterials primarily on auxetic materials which are automatically adjustable with strength and thickness in response to the applied forces as they have memorial ability to return to its original state on dissipation of the stresses. Here, the main emphasize is on biomedical applications of auxetic materials which comes under the category of 16 smart materials of the twenty first century having a great impact in biomedical area. The information provided through this review may be beneficial for the future development of biomedical devices and their clinical applications consequently improving the quality of patient's life.
Keywords: [No Keywords]